The relationship of nicotine dependence with serum leptin concentration and total calorie intake among healthy male smokers in Kota Bharu - Suhaimi, Muhammad Zulhusni (2015)
Cigarette smoking has been demonstrated to be associated with lower body weight and its cessation leads to weight gain. This action of smoking on body weight is believed to be nicotine mediated. Exposure to nicotine via tobacco smoking may disrupt leptin release and decrease feeding by increasing leptin concentration, thereby contributing to the inverse relationship between nicotine and body weight. The role of leptin as an appetite suppressor is believed to be responsible for weight changes among smokers. The aim of this study was to determine the association between nicotine dependence with serum leptin concentration and total calorie intake among healthy male smokers. This cross-sectional study was conducted in Universiti Sains Malaysia, Health Campus, Kelantan. Male smokers aged 20–50 years were purposively recruited. Smoking activity was measured by two methods which are through hair nicotine analysis and Fagerstrom Test for Nicotine Dependence (FTND) Questionnaire. Smokers were divided into low, moderate and high dependence according to Fagerstrom score. Fasting blood samples were collected from the subject and serum leptin concentration was measured by ELISA (a solid-phase two-site enzyme immunoassay). The total calorie intake of the subjects was assessed by 24-hour diet recall interview. A total of 107 subjects were enrolled. The mean age and BMI of the subjects were 37.00 (9.42) years and 24.59 (4.33) kg/m², respectively. The mean concentration of serum leptin and mean level of hair nicotine among low, moderate and highly nicotine dependent groups were not significantly different. There was a significant inverse correlation between the Fagerstrom score and serum leptin concentration (r=-0.198, p=0.048). However, there was no significant correlation between hair nicotine level and serum leptin concentration. The mean of total calorie intake among low, moderate and highly smoking dependence groups were significantly different (F(2,46)=3.688, p=0.03). However, there was no significant correlation between Fagerstrom score and hair nicotine level with total calorie intake. The present study showed that serum leptin concentration has a significant inverse correlation with Fagerstrome score. There was also a significant difference in the mean of total calorie intake between three groups of nicotine dependent where the highly dependent groups has the highest total calorie intake.